Active sound control in headphones - Ng, Bolin. (2009)
With the advancement in technology industry, problems caused by unwanted noise are becoming more evident, which can be seen from the increasing use of industry equipment and communication devices. In order to tackle such problems, noise control techniques, such as active noise control and adaptive noise cancellation are used. For an adaptive noise cancellation system, a primary and a secondary input signal are captured. The primary input signal Due to the complexity and the robustness of the system, feedforward control system is used for the implementation of the project. In addition, the system will incorporate the use of adaptive FIR filtering, as the system must be able to deal with unpredictable noise in the environment. For the hardware aspect of the project, ADSP-BF533 EZ-KIT Lite evaluation board is used for digital signal processing. VisualDSP++ is used to implement the software aspect of the project. Results were obtained from the system implementation. However, the results gathered were not ideal. This is due to the several problems that arise during the implementation. One of the main problems faced is the implementation of the adaptive algorithm. The algorithm must be properly implemented in order to achieve noise cancellation in headphones.